2023
DOI: 10.2459/jcm.0000000000001424
|View full text |Cite
|
Sign up to set email alerts
|

From the phenotype to precision medicine: an update on the cardiomyopathies diagnostic workflow

Abstract: Cardiomyopathies are disease of the cardiac muscle largely due to genetic alterations of proteins with ‘structural’ or ‘functional’ roles within the cardiomyocyte, going from the regulation of contraction-relaxation, metabolic and energetic processes to ionic fluxes. Modifications occurring to these proteins are responsible, in the vast majority of cases, for the phenotypic manifestations of the disease, including hypertrophic, dilated, arrhythmogenic and restrictive cardiomyopathies. Secondary nonhereditary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 99 publications
(259 reference statements)
0
2
0
Order By: Relevance
“…Diagnoses in these clinics are performed by the application of the recent algorithm proposed and supported by international experts and guidelines 3 . This was feasible thanks to the adoption over the last few years of all the diagnostic tools recommended: bone scintigraphy, CMR, and genetic testing for the presence of TTR mutations 3,18–21 . Our survey analysis also showed that the interviewed centers started to refer patients with confirmed ATTR-CA to the expert care center of Bologna in 2019 to continue their therapeutic path, with a decreasing trend of patients being referred to centers outside of the region.…”
Section: Discussionmentioning
confidence: 87%
“…Diagnoses in these clinics are performed by the application of the recent algorithm proposed and supported by international experts and guidelines 3 . This was feasible thanks to the adoption over the last few years of all the diagnostic tools recommended: bone scintigraphy, CMR, and genetic testing for the presence of TTR mutations 3,18–21 . Our survey analysis also showed that the interviewed centers started to refer patients with confirmed ATTR-CA to the expert care center of Bologna in 2019 to continue their therapeutic path, with a decreasing trend of patients being referred to centers outside of the region.…”
Section: Discussionmentioning
confidence: 87%
“…Improving awareness among healthcare professionals is crucial in the early detection and intervention of CA [ 20 , 21 , 22 ]. Primary care physicians and various specialists, including cardiologists, hematologists, neurologists, gastroenterologists, nephrologists, and orthopedics, are among those who should be made aware of CA.…”
Section: Improve Awarenessmentioning
confidence: 99%